Jesus and his world an archaeological and cultural dictionary - Rousseau, John J. 1930-; Arav, Rami (Minneapolis, MN Fortress Press, 1995)
Includes bibliographcial references and indexes.
Keywords: Christian antiquities -- dictionaries; Jesus Christ -- biography -- sources -- dictionaries; Israel -- antiquities -- dictionaries